2018
DOI: 10.2166/wst.2018.256
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of spiramycin fermentation residue using hyperthermophilic digestion: quick startup and performance

Abstract: This study aimed to evaluate the feasibility of hyperthermophilic anaerobic digestion at 70 °C in the pretreatment of spiramycin fermentation residue. By feeding municipal excess sludge under a solid retention time of 5 days, the hyperthermophilic digester was successfully started up within 3 days from mesophilic digestion by a one-step temperature increase from 35 to 70 °C. MiSeq sequencing showed the fast establishment of thermophilic fermenting bacterial communities in 3 days immediately after the temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…At present, hydrothermal pretreatment has been applied in the treatment of waste mother liquor from the antibiotic fermentation process [10]. Recently, we reported that hyperthermophilic anaerobic digestion process operated at 70°C for 7 d could simultaneously remove antibiotics, reduce antibiotic resistance genes (ARGs) and enhance the solubility of spiramycin fermentation residue [11]. To further improve efficiency and reduce processing time, the thermal hydrolysis process operated at more than 120°C [12,13] has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…At present, hydrothermal pretreatment has been applied in the treatment of waste mother liquor from the antibiotic fermentation process [10]. Recently, we reported that hyperthermophilic anaerobic digestion process operated at 70°C for 7 d could simultaneously remove antibiotics, reduce antibiotic resistance genes (ARGs) and enhance the solubility of spiramycin fermentation residue [11]. To further improve efficiency and reduce processing time, the thermal hydrolysis process operated at more than 120°C [12,13] has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Hygienisation is a prerequisite for the safe agricultural reuse of the anaerobic digestate and its solid or liquid fractions [12,38]. A separate pasteurisation step can be avoided when the anaerobic treatment itself is carried out at thermophilic temperatures at appropriate minimum retention times [12,[39][40][41][42].…”
Section: Vacuum Toilets and Anaerobic Digestionmentioning
confidence: 99%